FACTORS INFLUENCING THE ANTAGONISTIC BACTERIAL INTERACTION BETWEEN CYANOBACTERIA (Microcystis aeruginosa PCC7941 and Aphanizomenon sp. PCC7905) and Stenotrophomonas sp. - Azhari Hasby, Fahri
Harmful algal blooming (HAB) are the main issues in aquatic ecosystem, and so called harmful because they produce toxins such as microcystin and nodularin. One of the strategies to eradicate HAB is the usage of bacteria as predator for cyanobacteria. Yet, the use of bacteria still need further evaluation before being applied to field test. In this study, several interaction assays between Stenotrophomonas sp. and cyanobacteria (Microcystis aeruginosa PCC 7941 and Aphanizomenon sp. PCC 7905) with different environmental factors (nutrient availability and predator-prey ratio) were conducted. In addition to that, PCR assay to search for mlrA gene (microcystin degrading gene) was also done. For the nutrient availability test, the predator was grown on Luria Broth and BG-11 (supplemented with casitone) liquid medium, while for the predator-prey ratio the test was conducted in 1:1, 3:1, and 5:1 ratio. Stenotrophomonas sp. grown in rich nutrient condition (Luria Broth) had higher lytic activity (9.01 % chlorophyll-a exchange rate) on compared to the ones grown in BG-11 supplemented with casitone (-13.45 % chlorophyll-a exchange rate), representing low nutrient composition. Predator-prey ratio of 3:1 was the optimal ratio for the lytic activity of Stenotrophomonas sp. (12.47 % chlorophyll-a exchange rate) on Aphanizomenon sp. PCC 7905. Epifluorescence microscopy showed cell to cell contact lysis mechanism of the antagonistic interaction. This study indicate that environmental factors have high impact on effective antagonistic interaction of Stenotrophomonas sp. even though the PCR results suggests that Stenotrophomonas sp. does not possess the mlrA gene that enables it to degrade microcystin.